Changes in the groundwater levels and regimes in the taiga zone of Western Siberia as a result of global warming; Theoretical and Applied Climatology; Vol. 147, iss. 3-4 - Savichev O. G. Oleg Gennadievich; Moiseeva Yu. A. Yuliya Aleksandrovna; Guseva N. V. Natalia Vladimirovna (2022, 2022)
Title screen